1991
DOI: 10.1159/000267116
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Timolol on Human Retinal, Choroidal and Optic Nerve Head Circulation

Abstract: In a double-masked, randomized, placebo-controlled study, we evaluated the effect of topical timolol maleate 0.5% on the retinal, choroidal, and optic nerve head circulation in 5 healthy volunteer subjects. Changes in the pulsatile component of choroidal blood flow (PCBF) were determined from measurements of the ocular pulse wave. Changes in the retinal arterial blood flow rate (RBF) and optic nerve head capillary blood speed (CBS) were determined by laser Doppler velocimetry and monochromatic photography. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 16 publications
(28 reference statements)
2
27
1
1
Order By: Relevance
“…Regarding choroidal blood flow, our results agree with those of other investigators who studied the effect of timolol [10][11][12][13]. In ani mal studies, Parver et al [10], using the hy drogen washout technique, found that an intracameral injection of 5% timolol produced a significant decrease in choroidal blood flow in cats.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding choroidal blood flow, our results agree with those of other investigators who studied the effect of timolol [10][11][12][13]. In ani mal studies, Parver et al [10], using the hy drogen washout technique, found that an intracameral injection of 5% timolol produced a significant decrease in choroidal blood flow in cats.…”
Section: Discussionsupporting
confidence: 90%
“…Nonselective β-blocking agents were reported to reduce choroidal and optic nerve head blood flow velocities but not blood flow velocity in the CRA, while a selective β-blocking agent, betaxolol, had no effect on choroidal and optic nerve head blood flow velocities [2, 6]. Harris et al [7]found that betaxolol decreases retrobulbar vessel resistance, whereas nonselective β-blockers leave that same distal vascular resistance unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…All of the previous studies measured acute vascular effects of β-blockers. Two of them were performed on healthy subjects [2, 6]and the other [7]was performed on patients with normal-tension glaucoma. Great caution should be exercised when transferring the vascular data obtained from normal subjects to POAG patients, because the latter have a deficient autoregulation of retrobulbar blood flow [8].…”
Section: Discussionmentioning
confidence: 99%
“…There has been no report regarding the effects of travoprost, bimatoprost or tafluprost on ONH blood flow in humans as far as we know. It is reported that timolol either had no significant effect on or decreased ONH blood flow in humans (Yoshida et al, 1991;Tamaki et al, 1997aTamaki et al, , 1997bNetland et al, 1999;Haefliger et al, 1999;Lübeck et al, 2001). In contrast, carteolol, betaxolol and nipradilol reportedly increased ONH blood flow in humans (Tamaki et al, 1997a(Tamaki et al, , 1997bTamaki et al, 1999;Mizuno et al, 2002).…”
Section: Introductionmentioning
confidence: 99%